Pricing and fiscal policies : a study in method - Rosenstein-Rodan, P.N.; The Massachusetts Institute of Technology (London : Allen & Unwin, 1964)
This book is about economic and social problem of development
Includes bibliographical footnotes and index.
oo 27/08/2018
Loans
Keywords: Fiscal policy; India